Buffalo as a Vision of the Future: Sustainable Agribusiness for Latin American Food Security - Hernandez, Armando Pacheco; Bonilla-Landaverry, Gesly Anibal (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Bufalos production emerges as a strategic alternative within sustainable agribusiness, especially in tropical regions of Latin America, where environmental conditions favor their development. Unlike conventional livestock species, buffalo have greater productive and economic performance under dual purpose systems, which makes them a viable option for small and medium -sized rural producers. This study aims to analyze the technical and financial feasibility of incorporating buffalo in extensive grazing systems, highlighting its efficiency to transform high availability forages into tropics into quality meat and milk. This modality allows to operate with low production costs, generating stable income and reducing common risks in the livestock sector. In addition, the approach is aligned with the principles of sustainability, by promoting the rational use of natural resources and strengthening regional food security. The results suggest that the incorporation of buffalo into production systems not only improves the well -being of producers, but also promotes more resilient agricultural models, profitable and committed to the social and ecological environment. In this way, it is consolidated as a strategic option for rural economic development, contributing to the strengthening of agribusiness oriented to food production in Latin America.